Effectiveness Of E-Ktp Services At The Population And Civil Registration Service In Gorontalo Regency - Naki, Mohamad Rasid; Aneta, Asna; Tui, Fenti Prihatini Dance (Public Policy Journal, 2025)
This study aims to describe the effectiveness of E-KTP services at thePopulation and Civil Registration Office of Gorontalo Regency and identify thefactors that influence it. The study uses a descriptive qualitative approach withdata collection techniques through observation, interviews, and documentation.The effectiveness of the service is analyzed based on indicators of goalachievement, integration, and adaptation. The results of the study indicate thatalthough the E-KTP service has shown an increase in terms of the number ofrecordings and printing each year, there are still obstacles in terms of timelinessof service, data errors, and employee attitudes towards the community. Factorsthat influence service effectiveness include employee ability, expertise,knowledge, attitude, motivation, and work stress. This study concludes that theE-KTP service in Gorontalo Regency is not yet fully effective and requiresimprovements in aspects of human resources and service systems.